Macrophage Activation Syndrome-Associated Markers in Severe Dengue - Ab-Rahman, H.A.; Rahim, H.; AbuBakar, Sazaly; Wong, Pooi Fong (Ivyspring International Publisher, 2016)
Hemophagocytosis, a phenomenon of which activated macrophages phagocytosed hematopoietic elements was reportedly observed in severe dengue patients. In the present study, we investigated whether markers of macrophage activation syndrome (MAS) can be used as differential diagnostic markers of severe dengue. Two hundred and eight confirmed dengue patients were recruited for the study. Sandwich ELISA was used to determine serum ferritin, soluble CD163 (sCD163), and soluble CD25 (sCD25) levels. The population of circulating CD163 (mCD163) monocytes was determined using flow cytometry. Receiver operating characteristic (ROC) analysis was plotted to determine the predictive validity of the biomarkers. Serum ferritin and sCD163 were found significantly increased in severe dengue patients compared to dengue fever patients (P = 0.003). A fair area under ROC curves (AUC) at 0.72 with a significant P value of 0.004 was observed for sCD163. sCD25 and mCD163 levels were not significantly different between severe dengue and dengue fever patients. Our findings suggest that in addition to serum ferritin, sCD163 can differentiate severe dengue from that of dengue fever patients. Hence, sCD163 level can be considered for use as a predictive marker for impending severe dengue.